Long-Term Follow-Up of HLA-A2+ Patients with High-Risk, Hormone-Sensitive Prostate Cancer Vaccinated with the Prostate Specific Antigen Peptide Homologue (PSA146-154) - Supriya Perambakam; Hui Xie; Seby Edassery; David J. Peace (Clinical and Developmental Immunology)
Twenty-eight HLA-A2+ patients with high-risk, locally advanced or metastatic, hormone-sensitive prostate cancer were immunized with a peptide homologue of prostate-specific antigen, PSA146-154, between July 2002 and September 2004 and monitored for clinical and immune responses. Fifty percent of the patients developed strong PSA146-154-peptide-specific delayed-type hypersensitivity skin responses, tetramer and/or IFN-γ responses within one year. Thirteen patients had stable or declining serum levels of PSA one year post-vaccination. A decreased risk of biochemical progression was observed in patients who developed augmented tetramer responses at six months compared to pre-vaccination levels (P=.02). Thirteen patients have died while 15 patients remain alive with a mean overall survival of 60 months (95% CI, 51 to 68 months) per Kaplan-Meier analysis. A trend towards greater overall survival was detected in men with high-risk, hormone-sensitive CaP who developed specific T-cell immunity following vaccination with PSA146-154 peptide.